2021
DOI: 10.3390/agronomy11061063
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Pandemic and Food Waste: An Empirical Analysis

Abstract: This paper investigates the impact of Covid-19 pandemic on food waste using an original dataset from 176 agrifood business operators in the European Union (EU). Our objective is to assess whether and why the pandemic crisis affected food waste level. Unlike previous studies that addressed the issue at a consumer level, our research focuses on pre-consumption waste covering stages of the agrifood supply chain from input suppliers to retailers. Considering the importance of waste reduction for the sustainability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…After the outbreak of the COVID-19, overstocked problems were observed around the globe. According to the shock transmission theory, the consequences of a shock are borne by the least elastic [ 44 ]. In our analysis, producers reported severe overstocked problems during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the outbreak of the COVID-19, overstocked problems were observed around the globe. According to the shock transmission theory, the consequences of a shock are borne by the least elastic [ 44 ]. In our analysis, producers reported severe overstocked problems during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Fundamental infrastructure and effective mechanisms of the food system always matter [ 44 ]. Except for some disruption in the short term, the food supply system in China performed remarkably well during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously stated, all phases of the food supply chain generate food waste, according to different factors. Some scholars studied the effects of the pandemic on the production of waste in all phases of the food supply chain, from production to consumption (Aldaco et al, 2020 ; Blazy et al, 2021 ; Boyacι-Gündüz et al, 2021 ; Cariappa et al, 2021 ; Di Marcantonio et al, 2021 ; Galanakis, 2020 ; Rejeb et al, 2020 ). Other scholars focused on particular stages of the supply chain (with the majority focusing on the consumption stage), or specific sectors (e.g., hospitality), reflecting on both the impact of the pandemic on food waste and future strategies to increase resilience (Filimonau, 2021 ; Strotmann et al, 2021 ).…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…In addition, Galanakis ( 2020 ) highlighted that the employment of such technologies to improve farming, post-harvest, storage, and transportation could ultimately reduce food waste. Di Marcantonio et al ( 2021 ) also identified the role of technological tools in influencing the generation of food waste, alongside sales channel disruptions and changes in public policy. In particular, the authors noted that technological tools that improve firms’ ability to adapt to new societal dynamics and public policies that mitigate shocks in the food supply chain (which have a negative impact on food waste) may contribute to decreasing food waste.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%